2015
DOI: 10.1080/09205063.2015.1049044
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and preliminaryin vitroevaluation of a bFGF-releasing heparin-conjugated poly(ε-caprolactone) membrane for guided bone regeneration

Abstract: In an effort to improve guided bone regeneration (GBR), we successfully fabricated a novel basic fibroblast growth factor (bFGF)-releasing heparin-conjugated poly(ε-caprolactone) membrane (hep-PCL/bFGF). This material has a porous microstructure with smooth and rough pore walls before and after heparinization, respectively. Our FTIR analyses indicated that chemical bonds were formed between PCL and heparin with a new amide C=O band at 1660 cm(-1) and a band at 3400 cm(-1) that can be attributed to -OH stretchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Furthermore, it has been proven that extracellular matrix (ECM) proteins (mainly collagen, fibronectin, laminin and vitronectin) (Müller et al, 2006;Rico et al, 2009;Chen et al, 2018), their RGD sequence (Arg-Gly-Asp) (Mörke et al, 2017) and cytokines [e.g., basic fibroblast growth factor (bFGF)] (Cao et al, 2015) have the capacity to promote cell attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been proven that extracellular matrix (ECM) proteins (mainly collagen, fibronectin, laminin and vitronectin) (Müller et al, 2006;Rico et al, 2009;Chen et al, 2018), their RGD sequence (Arg-Gly-Asp) (Mörke et al, 2017) and cytokines [e.g., basic fibroblast growth factor (bFGF)] (Cao et al, 2015) have the capacity to promote cell attachment.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction results in the damage of blood cellular membrane or the erythrocytes lysis leading to the release of their intracellular hemoglobin. The amount of released hemoglobin should be small to ensure the absence of toxicity of the implanted material . Moreover, hemocompatibility of membranes in contact with bone tissue could affect osseointegration .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in addition to improved hemocompatibility, results showed that heparin could affect the functions of osteoblast cells, such as osteoblast‐like MC3T3‐E1 . For instance, Cao et al studied on the GBR membrane based on PCL containing basic fibroblast growth factor and heparin . They showed that heparin‐PCL membrane exhibited larger projected areas than PCL one which was appropriate for osteoblast like cells to attach, proliferate, and differentiate.…”
Section: Introductionmentioning
confidence: 99%
“…The basic fibroblast growth factor-releasing heparin-conjugated PCL membrane has been successfully developed and exhibits biocompatibility. This basic fibroblast growth factor-releasing PCL membrane promotes human osteoblast-like cell attachment, proliferation and differentiation as compared with the naïve PCL membrane [79]. Metronidazole-incorporated PCL-based membranes decrease inflammatory response, determined in subcutaneous implantation model as compared to the unmodified PCL membrane [40,80].…”
Section: Polycaprolactone In Guided Tissue Regenerationmentioning
confidence: 96%